Body as Danger: Gender, Race and Body in Toni Morrison's Sul - Pi-hua Ni (Ilha do Desterro)
This paper aims at tackling the question as to why Sula as a social nonconformist and sexual dissident ends up as an avatar of evil, a powerless victim of witch-hunt and eventually a scapegoat for the decline and misfortunes of her community. To facilitate this critical task, this paper shall irst apply Michel Foucault’s genealogy of “the body as the bearer of pleasure and desire” as laid out in Abnormal to illustrate that Christian folks in Sula’s community interpret Sula’s nonconformity as evil and treat her as a danger to their social order. Thus, this paper argues that the black folks’ ostracism of Sula betokens their mass hysteria and witch-hunt to exorcise their community of danger and evil. Moreover, this paper suggests that Sula is gendered and racialized as a black witch and symbolically executed. In conclusion, this paper contends that an identiication of body with lesh, a phallocentric gender ideology and race bias converge into the black folk’s association of Sula with a witch and a danger and their subsequent victimization of sula as a scapegoat for all the misfortunes of their community.